Erlend Gehlken, Weather Omens of “Enūma Anu Enlil”: Thunderstorms, Wind and Rain (Tablets 44-49) (Cuneiform Monographs 43; Leiden: Brill, 2012) - Drawnel, Henryk (The Biblical Annals, 2015)
Book review: Erlend Gehlken, Weather Omens of “Enūma Anu Enlil”: Thunderstorms, Wind and Rain (Tablets 44-49) (Cuneiform Monographs 43; Leiden: Brill, 2012). Pp. x, 286. Pl. 47. € 105. ISBN 978-90-04-22588-6.